A Code Form Game in a Selection Process - Ferreira, M. A. M.; Matos, M. C. P. (EasyChair Preprint Nº 8205, 2025)
The aim of this paper is to present, in the scope of game theory, a new games representation: the code form, consisting of a table which contains the whole information, without any suppression or “adulteration “with regards to the game. After the theoretical description, its application is exemplified in solving the problem of selecting a candidate up to his/her acceptance trough game theory. The originality this paper proposes is how this problem will be approached: it will be treated as a single game which is made up of two parts, going as far as to state that the payoffs in the first part of the game will be the mediators of the second part of the game, instead of using the stochastic dynamic programming approach. The solution of the problem using stochastic dynamic programming is also presented to highlight empirically the parallelism between the two modes of resolution.